Controlling climate change - Metz, Bert (Cambridge University Press, 2010)
"An unbiased and comprehensive overview, based on the findings of the IPCC (Intergovernmental Panel on Climate Change). Using no jargon, it looks at tackling and adapting to man-made climate change, and works through the often confusing potential solutions. Bert Metz is the former co-chair of the IPCC, at the center of international climate change negotiations. His insider expertise provides a cutting edge assessment of issues at the top of the political agenda. He leads the reader succinctly through ambitious mitigation scenarios, in combination with adapting our future societies to different climate conditions and the potential costs of these measures. Illustrations and extensive boxed examples motivate students to engage with this essential global debate, and questions for each chapter are available online for course instructors. Minimal technical language also makes this book valuable to anyone with an interest in action to combat climate change"--Provided by publisher.